2010 Forum on Specification &Amp; Design Languages (FDL 2010) 2010
DOI: 10.1049/ic.2010.0134
|View full text |Cite
|
Sign up to set email alerts
|

Tiny-: a novel formal method for specification. Analysis, and verification of dynamic partial reconfiguration processes

Abstract: On FPGA-platforms, the feature of dynamic partial reconfiguration offers a wide range of applications. We propose a new formal method for design, analysis, and verification of the reconfiguration process on such devices. The π-calculus, also known as the calculus of mobile processes, is a type of process algebra typically used to describe dynamic communicating processes. We propose the π-calculus as a foundation to model dynamic partial reconfiguration of hardware modules. A subset of this calculus that we cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Formal verification can also be used at system design time. The tiny pi-calculus approach applies a subset of pi-calculus to formally model the reconfiguration rules/directives (i.e., when to reconfigure what) of a DRS design [Seffrin et al 2010]. Symbolic simulation has been used to verify reconfigurable streaming applications meet their executable software specification [Todman et al 2012].…”
Section: Related Workmentioning
confidence: 99%
“…Formal verification can also be used at system design time. The tiny pi-calculus approach applies a subset of pi-calculus to formally model the reconfiguration rules/directives (i.e., when to reconfigure what) of a DRS design [Seffrin et al 2010]. Symbolic simulation has been used to verify reconfigurable streaming applications meet their executable software specification [Todman et al 2012].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, n + 1 queue activity cycles would be required to transmit n arguments in the monadic calculus, while only one cycle is required in the polyadic rr-calculus. (11) x (a,b,c) == x(w).w(a).w(b).w(c) (13) 3) Complex System Example: In the example given by Equation 14, three additional features are introduced. Firstly, the name y of the receiving link y (w) is bound.…”
Section: ) System With Persistence Operator and Dynamic Partialmentioning
confidence: 99%
“…Communication is implemented by an interconnect network, which is also controlled by the schedule. Execution of the schedule can be performed by a softcore processor, as has been shown in [11], but direct execution in hardware would eliminate this requirement. In [10], it has been shown that an existing ticalculus verification tool can be used for proving properties of the reconfiguration schedule.…”
Section: Introductionmentioning
confidence: 99%